1978
DOI: 10.1037/0022-0663.70.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and crystallized intelligence and broad perceptual factors among 11 to 12 year olds.

Abstract: A battery of 36 visual and auditory tests was given to a sample of 113 primary school children. Second-order analysis of the data yielded two well-defined factors representing Fluid (Gf) and Crystallized (Gc) Intelligence and two perceptual factors corresponding to General Visualization (Gv) and General Auditory Function (Ga). Perceptual factors were not clearly separated from broad intellective factors at this age level. Factor analyses of large batteries of tests consisting of markers for the well-replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
(15 reference statements)
2
22
0
Order By: Relevance
“…Cattell (1982b) resolved this apparent discrepancy by factor analyzing Thurstone's primary mental ability intercorrelations, and found that at the higher-order level, general factors (Gf and Gc) emerged (cf. Boyle, 1988b;Stankov, 1978Stankov, , 1983Stankov, , 1986Stankov & Chen, 1988;Stankov, Horn, & Roy, 1980). Hence, both Spearman's and Thurstone's findings were compatible, but represented different levels of the hierarchical structure of abilities.…”
Section: Factor Analysis Of Intellectual Abilitiessupporting
confidence: 68%
“…Cattell (1982b) resolved this apparent discrepancy by factor analyzing Thurstone's primary mental ability intercorrelations, and found that at the higher-order level, general factors (Gf and Gc) emerged (cf. Boyle, 1988b;Stankov, 1978Stankov, , 1983Stankov, , 1986Stankov & Chen, 1988;Stankov, Horn, & Roy, 1980). Hence, both Spearman's and Thurstone's findings were compatible, but represented different levels of the hierarchical structure of abilities.…”
Section: Factor Analysis Of Intellectual Abilitiessupporting
confidence: 68%
“…Another possibility is suggested by our previous work with auditory tests (e.g. Horn and Stankov, 1981;Stankov, 1978). Auditory variables in this work define a broad auditory function, Ga, which transcends tonal quality and involves perception of rhythm and perception of distorted or distracted speech.…”
Section: First-order Factorsmentioning
confidence: 99%
“…The tests were selected in such a way that they might serve to define four well-replicated primary factors in Gf/Gc theory (Horn, 1973;Horn and Stankov, 1981;Stankov, 1978;1979;. It was hoped that the emergence of a clear factorial structure in the single tests would serve as a basis for comparison with previous studies which have used these tests and also as a basis for comparison with results involving competing tasks.…”
Section: Test Battery-sing!e Testsmentioning
confidence: 99%
“…First, the factor structure of abilities and personality is remarkably similar across different racial and ethnic groups (Cattell, 1987a;Jensen, 1980). Thus, the structure of auditory abilities has been replicated in the USA , Yugoslavia (Stankov, 1978), and Australia (Stankov & Spilsbury, 1978). Likewise, the 16PF personality structure has been replicated crossculturally (see Cattell, 1973).…”
Section: Crosscultural Differences In Traditional Tests Of Personalitmentioning
confidence: 77%